The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0203486
|View full text |Cite
|
Sign up to set email alerts
|

Liver elasticity in healthy individuals by two novel shear-wave elastography systems—Comparison by age, gender, BMI and number of measurements

Abstract: ObjectiveEstablishing normal liver stiffness (LS) values in healthy livers is a prerequisite to differentiate normal from pathological LS values. Our aim was to define normal LS using two novel elastography methods head-to-head and to assess the number of measurements, variability and reproducibility.Materials and methodsWe evaluated shear wave elastography (SWE) methods integrated in Samsung RS80A and GE S8 by obtaining LS measurements (LSM) in 100 healthy subjects (20–70 years). Transient Elastography (TE) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
27
7
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 32 publications
7
27
7
1
Order By: Relevance
“…We found that higher age was most strongly associated with advanced hepatic fibrosis in both the logistic regression and decision‐tree analyses. However, the previous study showed that age is not associated with an increase in liver stiffness . This result differs from the present result, and this might be attributed to the number and characteristics of enrolled participants.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We found that higher age was most strongly associated with advanced hepatic fibrosis in both the logistic regression and decision‐tree analyses. However, the previous study showed that age is not associated with an increase in liver stiffness . This result differs from the present result, and this might be attributed to the number and characteristics of enrolled participants.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the previous study showed that age is not associated with an increase in liver stiffness. 26 This result differs from the present result, and this might be attributed to the number and characteristics of enrolled participants. In the previous study, the number of participants was 20 in the group aged ≥61 years, and no participants aged ≥71 years were enrolled.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations